Characterization of Sodium Channel Mutations in the Dengue Vector Mosquitoes Aedes aegypti and Aedes albopictus within the Context of Ongoing Wolbachia Releases in Kuala Lumpur, Malaysia - Noor Afizah Ahmad; Nancy M. Endersby-Harshman; Nur Ruqqayah Mohd Mazni; Nur Zatil Aqmar Mohd Zabari; Siti Nor Syazwani Amran; Muhammad Kamarul Ridhuan Ghazali; Mohd Arif Abdul Karim; Yoon Ling Cheong; Steven P. Sinkins; Nazni Wasi Ahmad; Ary A. Hoffmann (Insects, 2020)
Specific sodium channel gene mutations confer target site resistance to pyrethroid insecticides in mosquitoes and other insects. In Aedes mosquito species, multiple mutations that contribute to resistance vary in their importance around the world. Here, we characterize voltage sensitive sodium channel (Vssc) mutations in populations of Aedesaegypti from Kuala Lumpur, Malaysia, and look at their persistence in populations affected by ongoing Wolbachia releases (a dengue control measure). We also describe a Vssc mutation in Aedesalbopictus (F1534L) found for the first time in Malaysia. We show that there are three predominant Vssc haplotypes in Aedesaegypti in this region, which all persist with regular backcrossing, thereby maintaining the original genetic composition of the populations. We identify changes in genotype frequency in closed populations of Ae. aegypti maintained for multiple generations in laboratory culture, suggesting different fitness costs associated with the genotypes, some of which may be associated with the sex of the mosquito. Following population replacement of Ae. aegypti by Wolbachia in the target area, however, we find that the Vssc mutations have persisted at pre-release levels. Mosquitoes in two genotype classes demonstrate a type I pyrethroid resistance advantage over wildtype mosquitoes when exposed to 0.25% permethrin. This resistance advantage is even more pronounced with a type II pyrethroid, deltamethrin (0.03%). The results point to the importance of these mutations in pyrethroid resistance in mosquito populations and the need for regular backcrossing with male mosquitoes from the field to maintain similarity of genetic background and population integrity during Wolbachia releases.